A Nonmetal‐Containing Nitric Oxide Donor Activated with Single‐Photon Green Light. Issue 38 (9th June 2017) - Blangetti, Marco; Fraix, Aurore; Lazzarato, Loretta; Marini, Elisabetta; Rolando, Barbara; Sodano, Federica; Fruttero, Roberta; Gasco, Alberto; Sortino, Salvatore
Abstract: Using a facile synthetic route, an organic NO release agent based on a BODIPY light‐harvesting antenna was devised. This compound is stable in the dark and delivers NO under photoexcitation with biologically favorable green light. Temporally regulated vasodilation capability is demonstrated on rat aorta by green‐light‐induced NO release. Abstract : NO? Yes ! Using a facile synthetic route, an organic NO release agent based on a BODIPY light‐harvesting antenna was devised. This compound is stable in the dark and delivers NO under photoexcitation with green light.